Swimming pool-associated viral outbreaks in China: causes and solutions - Huang, Zheng (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to assess the causes of the swimming pool-associated viral outbreaks in China and discuss the possible preventive measures for the outbreaks.MethodsA systematic search was performed in 4 Chinese and English databases for studies investigating the swimming pool-associated viral outbreaks in China up to June 2024.Results29 outbreaks were included in the review. A median of 89 cases per outbreak was observed among 29 outbreaks, and most outbreaks (27/29, 93%) were caused by adenovirus. The findings regarding the difference in attack rate of adenovirus between males and females were not consistent. Poor maintenance and management of the pool (26/29, 90%), difficulty in early identification of outbreaks (21/29, 72%), and lack of public awareness of waterborne diseases (7/29, 24%) were the main causes of the outbreaks.ConclusionThis review reveals the causes of swimming pool-associated viral outbreaks in China, and possible preventive measures could include improving pool maintenance and management, early recognition of the outbreaks, and increasing public awareness of recreational water illnesses.